LITERAL AND DENOTATIVE MEANING OF ENGLISH SLAG IN TIKTOK TRENDS AMONG GEN Z - Olivia Damanik; Nauli Hosianna Napitu; Dewi Hutapea; Dumaris E Silalahi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Language continues to evolve dynamically in the digital era, particularly through social media platforms that facilitate creativity and identity expression. This study investigates the semantic dimensions of English slang used by Generation Z on TikTok, focusing on the relationship between literal and denotative meanings. Using a qualitative descriptive method, data were collected from TikTok videos uploaded between 2023 and 2025 that contained English slang expressions frequently used in online communication. Thirty slang words such as rizz, no cap, slay, tea, and vibe were analyzed through semantic comparison and contextual interpretation. The findings reveal significant semantic shifts including broadening, metaphorical extension, and innovation, demonstrating how Gen Z reconstructs meaning to express emotion, humor, and social belonging. Slang on TikTok functions not only as linguistic creativity but also as a socio-cultural code that reflects self-presentation, digital identity, and community solidarity. These findings align with recent linguistic theories emphasizing language as a social semiotic system and support contemporary research (Keidar et al., 2022; Nurhayati & Putri, 2024; Syafaah & Haryanto, 2024) that highlights the participatory nature of online language change. Overall, the study contributes to understanding how English slang evolves in digital environments and how Generation Z shapes modern linguistic innovation through social media interaction. Keywords: Slang, TikTok, Generation Z, Literal, Denotative